Prevalence of psychosexual problems in patients attending a genitourinary clinic. Issue 6 (December 1984) - Slatford, K; Currie, C
Abstract : The prevalence of self reported psychosexual problems in 265 men and 160 women who attended the genitourinary clinic at this hospital was assessed. Twenty-six (10.6%) men and 13 (9.0%) women had sexual problems either as an individual or within their regular relationship. The highest prevalence of problems was in married or cohabiting women and men, both homosexual and heterosexual, over 30.